2013
DOI: 10.7314/apjcp.2013.14.12.7569
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of a Phase I/II Study of Simultaneous Boost Irradiation Radiotherapy for Locally Advanced Nasopharyngeal Carcinoma

Abstract: 7%) showing partial remission.The most frequently observed acute toxicities during the concurrent chemoradiotherapy were mucositis and leucopenia. Four patients (6.9%) had RTOG grade 3 mucositis, whereas four patients (6.9%) had grade 3 leucopenia. No patient had grade 4 acute toxicity. Three (5.17%) of the patients exhibited injury to the brain on routine MRI examination, with a median observation of 32 months (range, 25-42months). All of them were RTOG grade 0. The 3-year overall, regional-free and distant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We found that conventional fraction intense-modulated radiotherapy reduced liver damage and encouraged more normal cell regeneration than hyperfractioned radiotherapy, according to radiation biology (Dimri et al, 2013). The use of IMRT may improve the ability to deliver high doses to the planned target volume while preserving the integrity of the surrounding normal tissues (Xiang et al, 2013). 5-Fu drugs can enhance radiosensitivity without increasing liver damage, according to many studies (Zeng et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…We found that conventional fraction intense-modulated radiotherapy reduced liver damage and encouraged more normal cell regeneration than hyperfractioned radiotherapy, according to radiation biology (Dimri et al, 2013). The use of IMRT may improve the ability to deliver high doses to the planned target volume while preserving the integrity of the surrounding normal tissues (Xiang et al, 2013). 5-Fu drugs can enhance radiosensitivity without increasing liver damage, according to many studies (Zeng et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…However, dose escalation has been found relevant with improved survival in previous studies (Wang, 1987). The use of IMRT has shown encouraging results with a survival rate of 60-62% at 5 years (Low et al, 2006;Seo et al, 2009;Koutcher et al, 2010;Chee Ee Phua et al, 2013;Phua Chee Ee et al, 2013;Xiang et al, 2013;).…”
Section: Discussionmentioning
confidence: 99%
“…But 5-year survival rate is only 40% and the recurrence rate could reach as high as 42% if only radiotherapy is considered because most patients with nasopharyngeal carcinoma are diagnosed with advanced disease ( . In recent years, studies have shown that most of local recurrence after radiotherapy of nasopharyngeal carcinoma (NPC) occurred within the field of radiation, and it is estimated that recurrence within the radiation field accounting for 60% of the total number of recurrence (Sun et al, 2013;Xiang et al, 2013;Xie et al, 2013;Abbasi et al, 2014;Cai et al, 2014;Cheah et al, 2014;Chen et al, 2014;Deng et al, 2014;. The existence of hypoxic cells may be one of the main factors that cause the failure of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%